An exploration of the correlation between stress and blood glucose levels in athletes: Strategies for maintaining peak performance - Haryanto; Saputra, Adhe; Muzaffar, Ahmad (Journal Sport Area, 2024)
Background Problems: Stress can cause a person to experience an accumulated risk of increased cholesterol and negatively impact performance in the field, as indicated by a decrease in blood glucose levels. Research Objectives: This research aims to identify the relationship between stress and blood glucose levels to find solutions for athletes to maintain glucose levels when competing. Methods: The research method was cross-sectional with an observational study approach. Glucose levels were assessed using an Accu-Chek device, while anxiety levels were assessed using the Perceived Stress Scale (PSS) questionnaire. The research subjects were 130 Provincial Training Camp (PELATPROV) athletes with an average age of 25.01 ± 5.15 years old, a weight of 64.15 ± 7.93 kg, a height of 171.21 ± 5.88 cm, and a BMI of 21.98 ± 3.71 kg/m2. Findings and Results: The results indicated significant differences in stress (0.001 < 0.05) and blood glucose levels (0.001 < 0.05) between the two groups. The pre-PON athlete group dominated the increase in stress and decrease in blood glucose levels compared to the non-Pre-PON group. Thus, this research has provided evidence of a correlation between stress levels and decreased blood glucose levels. Conclusion: Psychological and physiological aspects were proven to have an inevitable correlation. Athletes and coaches must communicate more deeply about the expected treatment during the preparation period, during and after the match, to understand each other’s needs to achieve performance. Therefore, athletes’ performance can be maintained well during competition and training.